The Relevance of Muhammad Naquib Al-Attas' Concept of Scientific Integration to the Scientific Development of State Islamic Religious Universities (PTKINN) in Indonesia - Ummulkhairy Ummulkhairy; Erba Rozalia Yulianti (FKIP - Universitas Riau, 2026)
Scientific integration has become a central agenda of State Islamic Religious Universities (PTKINN) in Indonesia, yet many institutional models remain stronger at the level of curriculum juxtaposition, symbolic linkage, and administrative transformation than at the level of epistemological reconstruction. This study aims to analyze the relevance of Syed Muhammad Naquib al-Attas' concept of scientific integration to the development of PTKINN scientific paradigms. Using library research, the study analyzes al-Attas' primary works on Islamization of knowledge, Islamic worldview, and ta'dib, supported by secondary literature, PTKINN policy documents, and previous studies on integration models. Content analysis identifies four core themes: Islamic worldview as the ontological foundation of knowledge, Islamization of knowledge as epistemological purification, ta'dib as pedagogical orientation, and dewesternization as methodological critique. Comparative analysis shows that al-Attas' concept contributes epistemologically by strengthening tawhid-based foundations, pedagogically by orienting higher education toward civilized Muslim intellectuals, and methodologically by providing critical procedures for examining secular assumptions in modern disciplines. The study concludes that al-Attas' thought can enrich PTKINN integration at policy, curriculum, and lecturer development levels when applied critically and contextually.